Neue Cassidinen aus China (Coleoptera: Chrysomelidae). - Medvedev, Lev N. (Contributions to Entomology = Beiträge zur Entomologie, 1957)
The results of the treatment of Chinese Cassidinae from the author's collection are discussed. There are described 3 new species, 2 new subspecies, and mentioned species new to China. Types and Paratypes in the collection of the Zool. Inst. Acad. Sei. USSR and in the author's collection.Nomenclatural Actsgresitti [sic!] Medvedev, 1957 (Basiprionota), spec. n.mongolensis Medvedev, 1957 (Cassida prasina), sspec. n.hincksi Medvedev, 1957 (Cassioa Mionycha), spec. n.gansuica Medvedev, 1957 (Glyphocassis spilota), sspec. n.pygmaea Medvedev, 1957 (Thlaspida), spec. n.